INHIBITION OF THE SECONDARY ANTIBODY RESPONSE IN VITRO BY SALICYLATE AND GENTISATE - Ambrose, Charles Tesch (The Rockefeller University Press, 1966)
Salicylate inhibition of the secondary antibody response initiated in vitro on day 0 has been studied in cultures of rabbit lymph node fragments. Levels of 1.25 to 1.5 mM (0.20 to 0.24 mg/ml) sodium salicylate present in serum-free medium throughout an 18- or 21-day culture period completely inhibit the secondary response. This inhibition is largely accomplished by the drug's action during the first 9 days, which corresponds to the inductive phase for this culture system. Relatively little inhibition is produced by adding the drug only after day 9, although over 90% of the antibody produced during a 21-day experiment is synthesized after day 9. Studies with media of different pH's show that this inhibition is more correctly a function of the nonionized salicylic acid concentration in the medium than of the total salicylate concentration. Arguments are presented against the possibility that salicylate at the levels used here inhibits antibody synthesis by uncoupling oxidative phosphorylation. Acetylsalicylic acid (aspirin) produces the same degree of inhibition in vitro as do equimolar concentrations of sodium salicylate. Gentisate (5-hydroxysalicylate) is 15-fold more effective in producing 50% inhibition than salicylate; its temporal pattern of inhibition is similar to that of salicylate.